Audit committee characteristics, enterprise risk management and stock price synchronicity. Issue 1 (17th November 2021) - Ghafoor, Zeshan; Ahmed, Irfan; Hassan, Arshad
Abstract : Purpose: This study aims to examine the impact of audit committee (AC) characteristics and enterprise risk management (ERM) on stock price synchronicity (SYNCH). Design/methodology/approach: Based on a sample of 437 US-based firms over the period 2010 to 2017, the current study uses fixed-effect and ordinary least square to test the formulated hypotheses. Majority of the sample firms are based on the S&P 500 index. This study also performs a battery of robustness checks. Findings: The authors find that overall female members and female financial experts and female chairpersons of the AC are negatively associated with SYNCH. Similarly, the study endorses the monitoring role of financial experts and the diligence of the AC (threshold of four annual meetings), as both are negatively associated with SYNCH. However, the authors find that the AC chaired by the financial expert is also negative but insignificantly associated with SYNCH. Finally, the study finds that ERM is also negatively linked with SYNCH. Practical implications: The findings of the current study offer some important policy implications. For instance, the shareholders can benefit from the monitoring abilities of women and financial experts by increasing their ratio in the AC. The study also offers some useful insights regarding the financial experts and chair of the AC and ERM. Originality/value: The current study examines the association of AC characteristics with SYNCH, while the prior literature only assesses the impact of various board characteristics (such as size, independence and gender diversity). The study also contributes to the literature of ERM by providing new insights on the influence of the presence of ERM framework/program on SYNCH.